THE EFFECTIVENESS OF USING VISUAL AUDITORY KINESTHETIC (VAK) LEARNING STYLE MODEL ON STUDENTS’ VOCABULARY MASTERY - Nasution, Qori Winda Auliya (Journal of Innovation in Research, Education and Culture (JIREC), 2025)
This study investigates the effectiveness of the Visual Auditory Kinesthetic (VAK) learning style model in improving students’ vocabulary mastery at SMP Asuhan Jaya Medan during the 2023/2024 academic year. A quantitative experimental research design was employed, involving 50 eighth-grade students divided into two groups: the experimental group (n = 25), which was taught using the VAK model, and the control group (n = 25), which received conventional instruction. Data were collected using a vocabulary test consisting of 20 items, including matching, gap-filling, and arranging tasks. Statistical analyses were performed using SPSS, including normality, homogeneity, and t-tests. The findings revealed that the experimental group’s post-test mean score (M = 84.24) was significantly higher than its pre-test mean (M = 32.52), and higher than the control group’s post-test mean (M = 78.68). An independent sample t-test confirmed a significant difference between the two groups (p < 0.05). These results suggest that the VAK model is more effective than conventional methods in enhancing vocabulary mastery. This study highlights the importance of incorporating multisensory approaches in English language teaching to support diverse learning preferences.Keywords: Visual Auditory Kinesthetic, Learning Style Model, Vocabulary Mastery